Atypical dopamine transporter inhibitors attenuate compulsive-like methamphetamine self-administration in rats. (15th March 2018) - Tunstall, Brendan J.; Ho, Chelsea P.; Cao, Jianjing; Vendruscolo, Janaína C.M.; Schmeichel, Brooke E.; Slack, Rachel D.; Tanda, Gianluigi; Gadiano, Alexandra J.; Rais, Rana; Slusher, Barbara S.; Koob, George F.; Newman, Amy H.; et al.
Abstract: Methamphetamine (METH) is a highly addictive drug, but no pharmacological treatment is yet available for METH use disorders. Similar to METH, the wake-promoting drug ( R )-modafinil (R-MOD) binds to the dopamine transporter (DAT). Unlike METH, R-MOD is not a substrate for transport by DAT and has low abuse potential. We tested the hypothesis that the atypical DAT inhibitor R-MOD and compounds that are derived from modafinil would decrease METH intake by reducing the actions of METH at the DAT. We tested the effects of systemic injections of R-MOD and four novel modafinil-derived ligands with increased DAT affinity (JJC8-016, JJC8-088, JJC8-089, and JJC8-091) on intravenous (i.v.) METH self-administration in rats that were allowed short access (ShA; 1 h) or long access (LgA; 6 h) to the drug. ShA rats exhibited stable METH intake over sessions, whereas LgA rats exhibited an escalation of drug intake. R-MOD decreased METH self-administration in ShA and LgA rats (in the 1st hour only). JJC8-091 and JJC8-016 decreased METH self-administration in both ShA and LgA rats. JJC8-089 decreased METH self-administration in LgA rats only, whereas JJC8-088 had no effect on METH self-administration in either ShA or LgA rats. These findings support the potential of atypical DAT inhibitors for the treatment of METH use disorders and suggest several novel compounds as candidate drugs. Highlights: There is currently no available pharmacological treatment for METH use disorder. Rats allowed extended access to METH escalate their drug intake. R-Modafinil and several modafinil analogues reduced escalated METH intake. Atypical DAT inhibitors have potential for treating METH use disorders.